РОЛЬ ЦЕЛЕВЫХ ПОКАЗАТЕЛЕЙ КАЧЕСТВА ОКРУЖАЮЩЕЙ СРЕДЫ В ОБЕСПЕЧЕНИИ ЭКОЛОГИЧЕСКОЙ БЕЗОПАСНОСТИ НАСЕЛЕНИЯ (Experimental biology, 2015)
The role of target indicators of quality of environment in maintenance of ecological safety of the population on an example of the Aktyubinsk area is shown. The data according to level of pollution of atmospheric air, soil, area waters is presented. The estimation of degree of risk of action of various pollutants on population health is carried out. Target indicators of quality of environment of the Aktyubinsk area are established.
Keywords: target indicator; environment